Interaction between settlement and shrinkage cracking in plastic concrete. (10th October 2018) - Combrinck, Riaan; Steyl, Lourens; Boshoff, William P.
Highlights: Five different cracking behaviours of plastic concrete have been identified. No cracking in conditions with low evaporation and differential settlement. Pure plastic settlement cracking show internal cracks and multiple surface cracks. Pure plastic shrinkage cracking shows sudden single cracking through the slap depth. Combining both cracks results in interaction and cracking long before expected. Abstract: The plastic period in conventional concrete is dominated by two volume changes namely, plastic settlement and plastic shrinkage, which if restrained can result in cracking. Although both volume changes and the resulting cracking have been well documented cracking during the plastic period remains a problem. One reason is the complex interaction between these cracks. This paper shows the necessity of considering the combined effect of plastic settlement and plastic shrinkage cracking when investigating the cracking of plastic concrete. This is achieved by isolating both cracking types individually, followed by the interaction between these cracks. Plastic settlement cracking shows multiple tensile surface cracks and shear induced cracks below the surface. Plastic shrinkage cracking shows a single well defined crack pattern which forms suddenly throughout the entire depth of the concrete. When combined significant crack widening can occur long before normally expected due to the negative synergy between these two crack types.